Hybrid Inspired Research on the Flying-Jumping Locomotion of Locusts Using Robot Counterpart - Wei, Dunwen; Gao, Tao; Li, Zhaoxin; Mo, Xiaojuan; Zheng, Shuqin; Zhou, Cong (Frontiers in Neurorobotics, 2019)
Locusts are a kind of agile insects that can move and maneuver so efficiently in the unstructured terrain and complex environment. This marvel survivability of locusts benefits from their flying and jumping multi-modal locomotion. But until recently, the main influences of the locomotion performance is still a controversial and unknown issue. In this paper, the ideas of hybrid inspired research combined biologically inspired robot with robot inspired biology was proposed and adopted to explore the principle of locust flying-jumping locomotion. we analyzed the influence of leg burrs and flapping wings on the jumping performance by the biological experiments. Nevertheless, individual heterogeneity and uncontrollability of locusts result in the unconvincing experimental results. Therefore, based on the idea of robotics-inspired biology, we proposed and built a locust-inspired robot with flying-jumping locomotion via the principle of metamorphic mechanism based on the biological-inspired robot. The idea of robotics-inspired biology remedied the shortcomings of biological experiments through the consistency and controllability of the robot experiments. Meanwhile, the preliminary experiments were carried out to validate our thought that the flapping wings and leg burrs of locust have a great influence on the jumping performance. Through the hybrid inspired research, the results show the leg burrs and flapping wings can help the locust jump longer and improve the stability by adjusting the landing attitude to some extent, and the biological experiments dedicate that the locust with leg burrs and wings have the self-stability ability.